ANALISIS YURIDIS TENTANG HARTA TIRKAH (HARTA PENINGGALAN) DITINJAU DARI SISTEM HUKUM KEWARISAN ISLAM ( STUDI PUTUSAN MA RI NO. 633 K/Ag/2013 ) - NIEKO INDHARWAN IRWAN (PREMISE LAW JURNAL, 2016)
A conflict often occurs between the parties who feel settled down peacefully and amicably. However, often this conflict cannot be settled down in such away and it should be settled down in the court. One of the conflicts which, in the end should be settled down in the court is the case in which a verdict has been handed down by the Judge of The Supreme Court of the Republic of Indonesia No.633 K/Ag/2013. In relief sought, the plaintiff principally begs the panel of judges to decide the land in disputes as the tirkah of the late and to declare that the bequest deed is void, to assign the plaintiff as the only heir and the shares of tirkah is conducted based on the Islamic inheritance law, adn to give the heir’s shares to the defendants, co-defendant I and co-defendant II as wasiatun wajibah. Based on the results of the analysis, it was found that the inheritance could be separated from the tirkah by firstly fulfilling the heir’s duties as regulated in the Article 175 of KHI. The solution for the tirkah sharing is that it should be started from fulfilling the heirs duties in form of the deceased’s tajhijsh, paying off his debts, returning one’s things that were left for safe keeping to the testator and carrying out his last will and testaments. The judge’s legal consideration in the verdict of the Supreme Court of The Republic of Indonesia No.633 K/Ag/2013 was not relevant to the Islamic inheritance law. Keywords: Tirkah, Islamic Inheritance Law, the Only Heir